دور التدريب في تحسين أداء العاملين بقطاع التعليم بمدينة بنغازي-ليبيا " دراسة ميدانية على عينة من الموظفين في مراقبة التعليم بنغازي " - الدروقي , زيـــاد ونيــس; المدني , محمـــود علي (Scientific Journal of University of Benghazi, 2022)
This study aimed at identifying the role of training in improving the performance of workers in Education Control in Benghazi. To achieve the objectives of the study, a descriptive approach was adopted. The study population consisted of 67 employees of the Education Control Benghazi (Administrative Affairs Department). Data on the subject of the study was collected via 56 forms that were distributed to 56 employees Out of these 56 forms, 50 were valid for analysis and 6 were excluded as not valid for analysis. Additionally, to analyze the data of the study and achieve its objectives, a statistical package for social sciences (SPSS) was used. The results of the study showed that 46% of the sample individuals were male and 54% were female which indicates a balance between the genders in the study, Through the obtained results of the study to test the main hypothesis and sub-hypotheses, the zero hypothesis for both the main hypothesis and the sub-hypotheses at the level of significance (0.05) was rejected, and the alternative hypothesis for both the main hypothesis of the study and sub-hypotheses was accepted, The results of the study show that there is a statistically significant relationship between the training and the performance of the workers in Education Control Benghazi. The study concluded with a number of recommendations, the most important of which are: The use of modern scientific methods in the dissemination of a culture of training for employees until the concept of training is concluded for them, Make training a continuous process to keep abreast of changes and developments in order to diversify skills and abilities.